Concept of Taqiyuddîn Al-Nabhâni and Abd Al-Qadîm Zallûm on Zakat Management for National Prosperity - Fahrurrozie, Rendra; Misno (Journal of Islamic Economics and Finance Studies, 2025)
This study explores the zakat management concepts of Taqiyuddîn Al-Nabhâni and Abd Al-Qadîm Zallûm in the context of national prosperity. It addresses two primary questions: (1) How does Al-Nabhâni conceptualize zakat for state welfare? and (2) How does Zallûm view zakat within a state framework? Utilizing a qualitative approach through library research and content analysis of their primary works, the study finds that both scholars emphasize the state's role in the collection and distribution of zakat through a centralized bait al-mal institution. While national priorities are acknowledged, the majority of zakat is intended for localized distribution to the eight eligible categories (asnaf) as outlined in Islamic law. The findings suggest that integrating classical Islamic frameworks into modern zakat administration can enhance public trust and governance. This model presents a potential alternative for improving zakat management in Indonesia, combining sharia compliance with institutional accountability and social impact.